Challenges and opportunities for CO2 electroreduction from a process systems engineering perspective - Dal Mas, Riccardo; Somoza-Tornos, Ana; Pérez-Fortes, Mar; Kortlever, Ruud; Kiss, Anton A. (Frontiers in Energy Research, 2024)
Despite the huge efforts devoted to the development of the electrochemical reduction of CO2 (ECO2R) in the past decade, still many challenges are present, hindering further approaches to industrial applications. This paper gives a perspective on these challenges from a Process Systems Engineering (PSE) standpoint, while at the same time highlighting the opportunities for advancements in the field in the European context. The challenges are connected with: the coupling of these processes with renewable electricity generation; the feedstock (in particular CO2); the processes itself; and the different products that can be obtained. PSE can determine the optimal interactions among the components of such systems, allowing educated decision making in designing the best process configurations under uncertainty and constrains. The opportunities, on the other hand, stem from a stronger collaboration between the PSE and the experimental communities, from the possibility of integrating ECO2R into existing industrial productions and from process-wide optimisation studies, encompassing the whole production cycle of the chemicals to exploit possible synergies.